NANDROLONE DECANOATE IS PROOXIDANT IN THE MYOCARDIUM OF EXERCISED OR SEDENTARY RATS - Pinheiro,Julyara Lima (2020)
ABSTRACT Introduction: Nandrolone decanoate is a synthetic testosterone analogue considered one of the most widely used anabolic androgenic steroids (AAS) among adolescents and athletes. Chronic ingestion of AAS increases the incidence of cardiovascular abnormalities in athletes, but the mechanism that causes these changes remains unknown. Objectives: The purpose of this study is to verify the possible effects of the use of anabolic androgenic steroids (AAS) on the morphology and oxidative metabolism of the heart in exercised and sedentary rats. Methods: This is a comparative prospective level II study. Twenty-four Wistar rats were distributed in groups that performed voluntary (TG) and sedentary (SG) running exercises, and used AAS: the Anabolic Training Group (ATG), and the Anabolic Sedentary Group (ASG). During the three months of the running protocol, the animals received an intramuscular injection of 5 mg/kg b.p. of AAS. After the training period, the rats were euthanized and the hearts were removed for evaluation of lipid peroxidation and antioxidant capacity, and for morphometric analysis. Results: The anabolic groups, ASG (0.3072 ± 0.0531) and ATG (0.2732 ± 0.0413), presented higher lipid peroxidation when compared to the non-anabolic groups SG (0.1705 ± 0.0224) and TG (0.1785 ± 0.0340). Conclusion: There was no change in total antioxidant capacity or in the thickness of the interventricular septum and left ventricular wall. Thus, the use of anabolic androgenic steroids did not cause morphological changes in the myocardium. However it did alter the oxidative metabolism. It was also verified that aerobic exercise had no protective effect against lipid peroxidation in the myocardium caused by the use of AAS. Level of evidence II; Prospective comparative study.